Analisis penggunaan metode springate (S-SCORE) Sebagai prediktor kebangkrutan (Studi pada Perusahaa Textile yang Terdaftar di Bursa Efek Indonesia pada Tahun 2011-2013) - Rahayu, Putri, Dra. Wafiatun Mukharomah, MM (2016)
The purpose of this study was to analyze the company's bankruptcy in the textile sector by using Model Sringate (S-Score) on the textile sector companies listed on the Indonesian Stock Exchange (BEI) 2011-2013. The population in this study are the financial statements of all Textile industry which is already listed on the Indonesia Stock Exchange (BEI) 2011-2013. Selection of the sample is determined by purposive sampling in order to obtain representative samples in accordance with the specified criteria. Data analysis method used is by using Springate. The results of this study indicate that Springate Model can be used to predict bankruptcy. Of the 10 companies that have done the research, there are nine companies that went bankrupt and the first company in good health. Nine companies are PT Argo Pantes Tbk, PT Century Textile Industry, PT Eratex Djaja Tbk, PT Panasia Indo Resources Tbk, PT Roda Vivatex Tbk, PT Sri Rejeki Isman PT Sunson Textile Manufacturer Tbk, PT Tifico Fiber Indonesia Tbk, PT Unitex Tbk , All nine companies have an average value of S-Score < 0.862 for three consecutive years. One company stated in a healthy condition/is not bankrupt is PT Trisula International. The company has an average value of S-Score > 0,862